MANAJEMEN KESISWAAN DALAM MENINGKATKATKAN PRESTASI AKADEMIK DAN NON AKADEMIK SISWA DI MAN 1 PESISIR BARAT - Megawati, Megawati; Yetri, Yetri; Fadillah, M. Kharis (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
In the context of educational institutions, the implementation of these management functions serves as the primary foundation for managing various aspects of education, including student management. Student management is an integral part of educational management, specifically focusing on managing students as the primary subjects in the educational process. This study aims to analyze student management based on the planning–actuating–controlling cycle in improving students’ academic and non-academic achievements at MAN 1 Pesisir Barat. This research used a qualitative descriptive approach involving the principal, vice principal of student affairs, teachers, homeroom teachers, and extracurricular supervisors. Data were collected through interviews, observations, and documentation and analyzed using an interactive model. The results show that planning has been systematically arranged through formal documents but is not fully based on students’ achievement data. Program implementation has been carried out fairly well through academic and non-academic activities, although challenges remain such as limited facilities and uneven student participation. Evaluation has been conducted regularly but has not been optimally used as a basis for decision-making. Therefore, student management has been implemented adequately but is not yet fully integrated into a data-driven management cycle.